Discourses of perfection representing cosmetic procedures and beauty products in UK lifestyle magazines - Hermans, Anne-Mette (New York, NY : Routledge, 2021)
This book explores editorial and advertising discourses related tocosmetic procedures and beauty products and services in UK lifestyle magazines, offering a holistic perspective on the normalisation of cosmetic procedures and the societal context in which particular perceptions haveflourished. The volume examines the societal climate that contributed to cultural perceptions of the body as object and project, and constructions of masculinities and femininities as context for developments in lifestyle magazines' content on beauty and cosmetic procedures. Integrating approaches from Critical Discourse Analysis, Thematic Analysis, and Content Analysis, Hermans explores the varying ways in which cosmetic procedures and other beauty products are marketed to different audiences andexamines phenomenasuch as the problem/solution rhetoric, and developments in beauty advertising discourse specifically targeted at men. The book also investigates the continuum view of beauty products and cosmetic procedures, and examines the implications of these blurredboundaries for the regulation of the cosmetic surgery industry. This innovative contribution to research on the representation of cosmetic procedures and beauty products in the media will be of interest to scholars researching at the intersection of language, gender, individualised body projects, and sexuality.
1. Creating and selling the malleable body 2. Cosmetic procedures 3. Methodology and project 4. Cosmetic procedures and beauty products/services in editorials and advertising 5. Cosmetic procedures and beauty products/services in advertising -- General 6. Cosmetic procedures and beauty products/services in advertising -- Medical and commercial aspects 7. Blurring boundaries 8. Negotiating masculinities in the beauty market 9. Concluding remarks
OCLC-licensed vendor bibliographic record.
Keywords: Feminine beauty (Aesthetics) -- Great Britain; Masculine beauty (Aesthetics) -- Great Britain; Cosmetics -- Social aspects -- Great Britain; Surgery, Plastic -- Social aspects -- Great Britain; Human body in advertising -- Great Britain; Women's periodicals, English; Beauty, Personal -- Social aspects -- Great Britain; HEALTH & FITNESS / Beauty & Grooming; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Linguistics